(untitled) - Hanks, Kurt (Boston, MA, 2006)
Rapid Viz, Third Edition: A New Method for the Rapid Visualization of Ideas provides hands-on instruction on quick sketching skills and techniques that allow you to picture your ideas mentally, and then quickly convert those thoughts into visual reality on a piece of paper. The method is not designed to help you become a master illustrator, but rather a visual thinker and communicator. Emphasizing speed and simplicity, the Rapid Viz method breaks down drawing to the essentials, teaching the fundamental techniques of graphic art and design using only the simplest of tools: felt-tip pens or pencils and paper. Using a minimum amount of time, trouble, and effort, Rapid Viz enables you to nail down your ideas onto paper, rapidly converting your thoughts while they are still fresh, and then polish them for clear visual communication with others
Keywords: Graphic arts,Felt marker drawing,Visual communication,Drawing, Psychology of,Vẽ kỹ thuật,Kỹ thuật đồ họa; Technique